Postharvest strategies for preventing flower wilting and leaf yellowing in cut Ranunculus flowers - Cavallaro, Viviana; Bulgari, Roberta; Florio, Francesco Elia; Restuccia, Pasquale; Vinci, Gianluca; Guffanti, Davide; Vignati, Sara; Ferrante, Antonio (Frontiers in Horticulture, 2023)
Appropriate postharvest treatment, as well as adequate conditions of storage, can be adopted to elongate lifespan of cut flowers. Thidiazuron (TDZ), a substituted phenylurea, and 1-methylcycloproene (1-MCP), a non-toxic inhibitor of ethylene perception, are nowadays substances commonly used to prevent early damages caused by senescence and to delay chlorophyll degradation. Ranunculus asiaticus L. is cultivated for cut flower production and it is highly sensitive to ethylene and leaf yellowing. Hence, this study was focused on analyzing the effect of different pulse treatments - TDZ 10 µM, 1-MCP 500 ppb, and a combination of them - applied for 24 hours after harvest. The aim of these treatments was in prolonging cut ranunculus flowers' vase life. The effect of treatments was evaluated by performing non-destructive (% loss of fresh weight, chlorophyll a fluorescence, in vivo chlorophyll content, and Nitrogen Flavonol Index – NFI) and destructive (chlorophyll, carotenoids, and anthocyanins concentration, phenolic index) analyses. Flower wilting was delayed of 4 days in 1-MCP + TDZ 10 µM treatments, which also reduced weight loss and chlorophyll degradation compared to the control. The effectiveness of these compounds in preventing senescence has been confirmed by the decreased biosynthesis of phenolic compounds.